The current status of oncolytic viral therapy for head and neck cancer - Matthew O. Old; Trisha Wise-Draper; Chadwick L. Wright; Balveen Kaur; Theodoros Teknos (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2016)
Objective: Cancer affects the head and neck region frequently and leads to significant morbidity and mortality. Oncolytic viral therapy has the potential to make a big impact in cancers that affect the head and neck. We intend to review the current state of oncolytic viruses in the treatment of cancers that affect the head and neck region. Method: Data sources are from National clinical trials database, literature, and current research. Results: There are many past and active trials for oncolytic viruses that show promise for treating cancers of the head and neck. The first oncolytic virus was approved by the FDA October 2015 (T-VEC, Amgen) for the treatment of melanoma. Active translational research continues for this and many other oncolytic viruses. Conclusion: The evolving field of oncolytic viruses is impacting the treatment of head and neck cancer and further trials and agents are moving forward in the coming years. Keywords: Head and neck squamous cell carcinoma, Oncolytic viruses, Clinical trials, Novel therapeutics